2021
DOI: 10.3390/ph14020151
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibition in Oesophago-Gastric Carcinoma

Abstract: Immune checkpoint inhibitors enrich the therapeutic landscape in oesophago-gastric carcinoma. With regard to oesophageal squamous cell carcinoma (ESCC), the selective PD-1 (programmed cell death receptor 1)-inhibitor nivolumab improves disease-free survival in the adjuvant therapy setting (CHECKMATE-577). In first-line treatment, ESCC patients (pts) benefit in overall survival (OS) from the PD-1-inhibitor pembrolizumab in combination with chemotherapy (KEYNOTE-590). In the second-line setting, nivolumab (ATTRA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
(63 reference statements)
2
18
0
Order By: Relevance
“…The disruption of the PD-1/PD-L1 interaction by immune checkpoint therapeutic antibodies (Abs) against PD-1 and PD-L1 reactivates antitumor T-cells, resulting in an antitumor effect [ 12 ]. Despite the great success of immune checkpoint therapies blocking the PD-1/PD-L1 interaction in a small subset of various cancer patients [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], the treatment failed in most cases, including in CRC patients, due to intrinsic unresponsiveness and/or acquired resistance [ 21 , 22 , 23 , 24 , 25 , 26 ]. Specifically, the early clinical trials demonstrated that patients with CRC appeared to be poor responders to immune checkpoint therapies [ 27 , 28 , 29 ], indicating an urgent need for novel immunotherapeutic strategies against CRC.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of the PD-1/PD-L1 interaction by immune checkpoint therapeutic antibodies (Abs) against PD-1 and PD-L1 reactivates antitumor T-cells, resulting in an antitumor effect [ 12 ]. Despite the great success of immune checkpoint therapies blocking the PD-1/PD-L1 interaction in a small subset of various cancer patients [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], the treatment failed in most cases, including in CRC patients, due to intrinsic unresponsiveness and/or acquired resistance [ 21 , 22 , 23 , 24 , 25 , 26 ]. Specifically, the early clinical trials demonstrated that patients with CRC appeared to be poor responders to immune checkpoint therapies [ 27 , 28 , 29 ], indicating an urgent need for novel immunotherapeutic strategies against CRC.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, cancer immunotherapy has demonstrated promising results with different types of tumors [9][10][11][12]. In particular, with the introduction of immune checkpoint inhibitor (ICI)-targeted immunotherapy, the immunotolerant tumor microenvironment can be overcome by reactivating T cells, enhancing anti-tumor immunity, and eliminating tumor cells more effectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Differential immune cell infiltration patterns in the 2 EC types may help explain their different response to ICIs. ESCC patients receiving a selective PD-1 inhibitor (i.e., nivolumab) showed improved disease-free survival in the adjuvant therapy setting (CHECKMATE-557) (45). In first-line treatment, PD-1-inhibitor (pembrolizumab) combined with chemotherapy significantly prolonged OS time for ESCC patients (KEYNOTE-590) (45).…”
Section: Discussionmentioning
confidence: 99%